1987
DOI: 10.1093/bja/59.12.1548
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Oxygen Tensions Measured Continuously in Patients Breathing 21% Oxygen and Nitrous Oxide or Air

Abstract: Changes in arterial oxygen tensions in nine anaesthetized patients during controlled ventilation with either 79% nitrous oxide in oxygen or air only, were measured continuously using an intra-arterial oxygen electrode. When the patients were ventilated with the mixture, there was a significant increase in PaO2 of 2.74 +/- 1.08 kPa (P less than 0.002) over control values obtained while the subjects were awake and breathing air spontaneously. Changing the inspired gas from nitrous oxide in oxygen to air while ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…All these factors were excluded in our study; diffusion hypoxia is a transient phenomenon, exhibiting a peak effect at 3 min after withdrawal of nitrous oxide. The existence of the phenomenon has been disputed, as postoperative desaturation may be explained by airway obstruction, ventilatory irregularity or changes in ventilatory volumes [6,7].…”
Section: Commentmentioning
confidence: 99%
“…All these factors were excluded in our study; diffusion hypoxia is a transient phenomenon, exhibiting a peak effect at 3 min after withdrawal of nitrous oxide. The existence of the phenomenon has been disputed, as postoperative desaturation may be explained by airway obstruction, ventilatory irregularity or changes in ventilatory volumes [6,7].…”
Section: Commentmentioning
confidence: 99%
“…Following the report which clearly indicated that N 2 O could be reduced electrochemically on silver contaminated surfaces, 70 other reports then began to appear on oxygen gas analysers failing dangerously in the presence of N 2 O, on blood-gas analysers becoming sensitive to N 2 O and so leading to the potential non-diagnosis of arterial hypoxaemia, 71,73 and on an intravascular P O 2 blood sensor grossly over-reading in patients breathing O 2 and N 2 O gas mixtures. 82,83 The intravascular blood P O 2 sensors which were commercially available in the 1970s often employed silver cathodes. Because silver has a much wider electrochemical reduction voltage window than Pt (at the same electrolyte pH), silver cathode P O 2 sensors were (and are) exquisitely sensitive to N 2 O, if the polarising potential is not kept low enough to escape the rising portion of the second reduction (N 2 O) wave (Fig.…”
Section: Nitrous Oxidementioning
confidence: 99%